Improving Reading Comprehension of Narrative Texts through Know, Want, Learn (KWL) Technique among Senior High School Students - Jumasri Jumasri; Jaraswat Trairat; Mehriban Safarova (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aimed to improve the reading comprehension skill of the eleventh-grade students of State Islamic Senior High School Palopo through the implementation of Know, Want, Learn (KWL) technique. The study focused on helping students understand narrative texts more effectively and increasing their active participation during the reading process. Methodology: This study used Classroom Action Research (CAR) consisting of two cycles: planning, acting, observing, and reflecting. The subjects were 26 students of class XI Natural science 1 State Islamic Senior High School Palopo. The instruments included observation sheets, interview lists, reading comprehension tests, and a camera for documentation. Data were analyzed using descriptive quantitative and qualitative methods. Main Findings: The findings showed that students’ reading comprehension improved after applying the KWL technique. In the first meeting of Cycle I, the mean score was 52.88, and in the second meeting it increased to 61.01. Students also showed better participation, stronger motivation, improved understanding of narrative texts, and greater confidence in completing the KWL chart activities. Novelty/Originality of this study: This study provides a practical classroom strategy by integrating the KWL technique into reading comprehension instruction for narrative texts. It emphasizes activating prior knowledge, setting reading purposes, and reflecting on learned information, which creates a more structured, student-centered, and interactive reading process for senior high school students.